2010
DOI: 10.1016/j.cemconres.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aggregate size and volume fraction on shrinkage induced micro-cracking of concrete and mortar

Abstract: In this paper, the influence of aggregate size and volume fraction on shrinkage induced micro-cracking and permeability of concrete and mortar was investigated. Nonlinear finite element analyses of model concrete and mortar specimens with regular and random aggregate arrangements were performed. The aggregate diameter was varied between 2 and 16 mm. Furthermore, a range of volume fractions between 0.1 and 0.5 was studied. The nonlinear analyses were based on a 2D lattice approach in which aggregates were simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(81 citation statements)
references
References 24 publications
6
75
0
Order By: Relevance
“…Although the aggregate can reduce the sorptivity because of its smaller sorptivity compared to cement paste, it can also increase the sorptivity because of the interfacial transition zone (ITZ), which is the zone between the cement paste and aggregate,. Recent studies reveal that the ITZ significantly affects air or water permeation through concrete but not the water absorption (Wong et al 2009;Grassl et al 2010;Bustos et al 2015). In terms of the mineral admixtures, the use of fly ash increases the sorptivity (Parrott 1992;Aurelia and Florea 2014;Liu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the aggregate can reduce the sorptivity because of its smaller sorptivity compared to cement paste, it can also increase the sorptivity because of the interfacial transition zone (ITZ), which is the zone between the cement paste and aggregate,. Recent studies reveal that the ITZ significantly affects air or water permeation through concrete but not the water absorption (Wong et al 2009;Grassl et al 2010;Bustos et al 2015). In terms of the mineral admixtures, the use of fly ash increases the sorptivity (Parrott 1992;Aurelia and Florea 2014;Liu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Severe drying, high temperature or low humidity, may induce microcracks in concrete. It is reported that the effect of these microcracks on the sorptivity is less, compared to those on the air and water permeabilities (Wong et al 2009;Grassl et al 2010). Therefore, as long as the amount of aggregate and mineral admixture are common, the sorptivity of concrete can be evaluated with the W/B, curing, and degree of drying.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have examined the influence of cracks on mass transport properties of concrete such as the work of Jacobsen et al [1996], Wang et al [1997], Gerald et al [1997,2000], Aldea et al [1999], Kamali-Bernard and Bernard [2009], Picandet et al [2009], Grassl et al [2010], Jang et al [2011], Akhavan et al [2012] and Djerbi et al [2008Djerbi et al [ , 2013. However, the majority of the available studies relate to large (> 0.1 mm) traversing cracks that go through the entire thickness of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate understanding the 52 underlying mechanisms causing microcracking, a number of experimental and numerical studies have been carried out 53 on model systems. These are essentially two-dimensional or very thin cementitious composites containing mono-sized 54 aggregate inclusions (glass spheres, steel rods) at relatively low volume fractions [18,[20][21][22][23]. These studies collectively 55…”
mentioning
confidence: 99%
“…A number of two-dimensional mesoscale models have also been presented in recent years to investigate the effect of 466 aggregates on drying shrinkage-induced microcracking [21][22][23]66]. These studies show that increasing the volume 467 fraction of inclusions yields an increase in degree of microcracking and size of the microcracks.…”
mentioning
confidence: 99%